Calcitriol Effect on Outcomes of in Vitro Fertilization in Infertile Women with Vitamin D Deficiency: A Double-Blind Randomized Clinical Trial - Doryanizadeh, Leila; Morshed-Behbahani, Bahar; Parsanezhad, Mohammad Ebrahim; Dabbaghmanesh, Mohammad Hossein; Jokar, Azam (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Introduction Recent studies have addressed the role of micronutrients in fertilization, such as vitamin D. The present study aims to explore the effects of using calcitriol, an active form of vitamin D, on IVF results in women with vitamin D deficiency.Method This double-blinded randomized clinical trial was done on 180 infertile women, undergone IVF treatment. Out of them, 95 were found to have vitamin D deficiency (blood serum 25-dihydroxy vitamin D <30 ng/ml). Fifty one women in experimental group were treated with two 0.25 µg calcitriol pills daily during 4 weeks (discontinued 8 hours prior to the embryo transfer) and 44 subjects to the placebo group (mean vitamin D deficiency 27.5 ±1.8 in case group vs. 27.6±1.8 in control group, P>0.05). Final analysis includes outcomes of chemical and clinical pregnancy was done on 74 women (including 36 in case and 38 in control group).Results Our study showed that in the experimental group, chemical pregnancy success was significantly higher than that in the control group, 31.4 vs. 18.2% (P<0.05). However, there were no significant differences between the 2 groups in reaching the clinical pregnancy stage (25.5% in case group vs. 13.6% in control group) and continuation of pregnancy into week 20 (9.8% in case group vs. 11.6% in control group) (P>0.05).Conclusion Calcitriol administration by improving the implantation process can significantly increase the chances of successful IVF cycle results in infertile women with vitamin D deficiency.
Keywords: calcitriol-IVF; infertility; pregnancy rate